2023
DOI: 10.31083/j.fbl2801018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Carnosine in Patients with Age-Related Diseases: A Systematic Review and Meta-Analysis

Abstract: Introduction: L-carnosine has been found to have multimodal activity. Aim: The aim of this review was to find out the efficacy of Lcarnosine in patients with age-related diseases. Methods: Clinical studies evaluated the effect of L-carnosine on cancer, cardiovascular disease, diabetes, and neurodegenerative disorders were searched in electronic bibliographic databases. The protocol has been registered with PROSPERO (CRD42022314033). The revised Cochrane risk of bias tool for randomized trials was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
(286 reference statements)
0
7
0
Order By: Relevance
“…Slowing the progression and improving the symptoms of certain neurodegenerative diseases, specifically AD and PD, has been confirmed sporadically in clinical trials in specific patient groups [ 59 , 60 , 61 , 64 ]. A meta-analysis of randomized trials confirmed the positive effect of carnosine supplementation (in doses of up to 1.5 g per day) in the Alzheimer’s Disease Assessment Scale and the Beck’s Depression Inventory [ 46 ]. Unfortunately, the number of clinical trials is very small.…”
Section: Carnosine Beta-alanine and Neurological Diseasesmentioning
confidence: 98%
See 4 more Smart Citations
“…Slowing the progression and improving the symptoms of certain neurodegenerative diseases, specifically AD and PD, has been confirmed sporadically in clinical trials in specific patient groups [ 59 , 60 , 61 , 64 ]. A meta-analysis of randomized trials confirmed the positive effect of carnosine supplementation (in doses of up to 1.5 g per day) in the Alzheimer’s Disease Assessment Scale and the Beck’s Depression Inventory [ 46 ]. Unfortunately, the number of clinical trials is very small.…”
Section: Carnosine Beta-alanine and Neurological Diseasesmentioning
confidence: 98%
“…A meta-analysis showed that supplementation with carnosine and beta-alanine led to reductions in fasting glycaemia, a decrease in HbA1c levels and insulin resistance [ 45 ]. Another meta-analysis including only randomized trials confirmed the effect of carnosine supplementation on DM patients, specifically on their HbA1c and fasting glucose levels [ 46 ]. This is supported by the results of yet another meta-analysis on 30 clinical trials of the effect of carnosine and related dipeptides in obese subjects, which showed reductions in fasting glycaemia and HbA1c, as well as reductions in obesity (waist circumference) [ 47 ].…”
Section: Carnosine Beta-alanine and Diabetes Mellitusmentioning
confidence: 99%
See 3 more Smart Citations